INTEGRASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN BAHASA INDONESIA DAN BAHASA INGGRIS UNTUK MENINGKATKAN LITERASI SEKOLAH DASAR - Surya Jagat, Lalu; Fazalani, Runi; Vitalia Hanako Murni Simanjuntak; Suci Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the integration of Islamic religious education values in Indonesian and English language learning to improve elementary school students’ literacy. The research employs a qualitative approach that focuses on descriptive data analysis from various documents. This approach was chosen because the study is based on literature review and library research. Data were collected through Google Scholar using keywords relevant to the research variables, and the selected journals were determined based on their relevance to those keywords. The findings indicate that the integration of Islamic educational values in Indonesian and English language learning at the elementary level is effective in improving students’ literacy. This improvement is reflected in students’ abilities in reading, writing, understanding information, and thinking critically. In Indonesian language learning, the use of texts containing Islamic values increases students’ reading interest, comprehension, and ability to express ideas in a structured manner. Meanwhile, in English language learning, the integration of values is implemented through vocabulary, dialogues, and simple contextual texts, which help improve students’ vocabulary mastery and comprehension, although challenges remain in pronunciation and self-confidence. In terms of writing, students show progress in constructing sentences that follow language rules and contain positive values. Additionally, students become more active in discussions, indicating that the integration of Islamic values not only enhances literacy skills but also shapes students’ attitudes and character. However, the implementation still faces several challenges, including limited teaching materials, a lack of variation in instructional media, and differences in students’ initial language abilities.